Factors influencing the orientation of the students in physical education major - Kiss, Zoltán (Acta Scientiarum Socialium, 2011)
Factors influencing the orientation of the students in physical education major. The aim of this research was to learn the motivation behind the choices physical education students made in their field of study. In our current research, which is a part of a larger project, we intended to find out whether the choice the students made in selecting their field of study was a result of their own decision, or parental influence, or the influence of their professors. We surveyed how much of the students’ efforts aimed towards getting a diploma, how important was the earning potential and whether they would like to be certified teachers in the future or not. The survey was based on a third degree Likert scale. The reason we chose this type was because we were able to process a larger amount by doing so, we could compare the answers and provide statistics. After evaluating the results, we concluded that the majority of the students would not mind teaching upon receiving their diploma, even they could picture themselves being in this path life long. The study involved surveying 159 physical education students from six universities (EJF, ELTE-TÓFK, KE-PK, NYME-MNSK, SZIE-ABK, SZTE-JGYPK) and took place between Fall 2008 and Fall 2010.
Keywords: motivation; professional orientation; Physical Education Studies